Hospitalizations for pediatric intoxication: a study from Istanbul - Akın, Yasemin; Ağzıkuru, Turgut; Cömert, Serdar; Atılkan, Pinar; Erdağ, Gülay Çiler; Telatar, Berrin (The Turkish Journal of Pediatrics, 2011)
The objective of this study was to describe the epidemiological features of pediatric patients hospitalized for intoxication. Data were collected from the medical records of children < or =14 years of age, admitted for intoxication in 2005-2007. Of the 2989 admissions, 330 (11%) were intoxication cases; 238 (72.1%) were